2014
DOI: 10.5815/ijitcs.2015.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Computing Trends in Saudi Arabia: An Exploratory Study

Abstract: Abstract-The main purpose of this research was to gain an understanding of the adoption behavior of mobile computing in Saudi Arabia. In particular, it aimed to acquire new insight into mobile computing trends, specifically in Saudi Arabia, in order to develop hypotheses and formulate precise criteria for mobile computing evaluation. In order to achieve these aims, the researcher created a focus group by recruiting eight participants with solid background knowledge of usability engineering and mobile computing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…An exploratory survey was used in the study due to it its potential towards contribution to generation of new theories [19] [20] especially in a topic like the one under this study that hardly has any studies on it. It was more suited for the study it is reported to be useful in less mature contexts, due its role in describing and establishing the basic understanding of a problem [21] [19] . Another reason for its use was its potential to focus on data reliability as result of obtaining it from a panel of experts [20] [19] when used with focused group as was the case in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An exploratory survey was used in the study due to it its potential towards contribution to generation of new theories [19] [20] especially in a topic like the one under this study that hardly has any studies on it. It was more suited for the study it is reported to be useful in less mature contexts, due its role in describing and establishing the basic understanding of a problem [21] [19] . Another reason for its use was its potential to focus on data reliability as result of obtaining it from a panel of experts [20] [19] when used with focused group as was the case in this study.…”
Section: Methodsmentioning
confidence: 99%
“…It was more suited for the study it is reported to be useful in less mature contexts, due its role in describing and establishing the basic understanding of a problem [21] [19] . Another reason for its use was its potential to focus on data reliability as result of obtaining it from a panel of experts [20] [19] when used with focused group as was the case in this study. The exploratory survey was most appropriate as it allowed for increasing the flexibility of the research design in order to provide for opportunities to explore different aspects of the context at hand [19] [22] .…”
Section: Methodsmentioning
confidence: 99%
“…The adaptation of mobile phone or mobile computing was initial in the beginning but it got the force from the some years later in Saudi Arabia (Alotaibi, 2015 ).By using mobile phone and mobile technology the personal ,social, governmental communication totally depended on this reliable technology but it has no long impact to development the human behavior (Campbell & Park, 2008).Mobile phone provided many positive features but we cannot neglect the negative influences inherited in mobile phone, one of the most common negative sides of smart phones is their side effects on human health and behavior (Abu-Shanab & Haddad , 2015).…”
Section: Related Workmentioning
confidence: 99%
“…Based on the findings of prior research that Mbusiness was more progressive than M-government in KSA [19], a general hypothesis was developed and put forward with eleven sub-hypotheses (derived from Nielsen's heuristics method [4]) to examine the different aspects of mobile software usability; to illustrate: Using the questionnaire, the sampled mobile software applications were evaluated by thirty-six (n=36) participants, all of which were regular mobile users. A balanced recruitment procedure was followed in order to control the effect of gender, knowledge and education of the participants.…”
Section: Empirical Studymentioning
confidence: 99%
“…In 2014, Alotaibi surveyed all mobile software applications that were developed by organizations in KSA, he identified a sample of thirty-six (n=36) mobile software applications -this should be regarded as a true representative sample of the population. Based on that argument [19], the thirty-six mobile software applications were considered for further analysis as a sample of the population; this sample can be viewed in Appendix A.…”
Section: Empirical Studymentioning
confidence: 99%